Characterizing neonatal vitamin D deficiency in the modern era: A maternal-neonatal birth cohort from Southern Europe. Issue 198 (April 2020) - Karras, Spyridon N.; Koufakis, Theocharis; Antonopoulou, Vasiliki; Goulis, Dimitrios G.; Annweiler, Cedric; Pilz, Stefan; Bili, Helen; Naughton, Declan P.; Shah, Iltaf; Harizopoulou, Vikentia; Zebekakis, Pantelis; Bais, Alkiviadis; et al.
Highlights: The study investigated maternal and neonatal determinants of neonatal vitamin D deificiency. A total of 129 mother-neonates pairs from Northern Greece were classified according neonatal vitamin D status at birth. Risk of neonatal deficiency was 6.89 increased for neonates of vitamin D deficient (<50 nmol/l) mothers. Use of alcohol during pregnancy was associated with a 5.5-fold higher risk for neonatal hypovitaminosis D. Abstract: Absence of adequate maternal vitamin D supplementation and decreased maternal ultraviolet exposure during pregnancy are key determinants for the manifestation of neonatal hypovitaminosis D at birth. These parameters may vary, according to country-specific dietary patterns, health policies and sunshine exposure. We aimed to investigate differences in calcium metabolism and anthropometric profiles according to neonatal vitamin D status at birth, in a sunny region of Northern Greece. A secondary aim was to identify maternal parameters as risk factors for developing neonatal vitamin D deficiency at birth. A total of 129 mother-neonate pairs were included in the study and classified into three groups, according to neonatal 25-hydroxy-D [25(OH)D)] concentrations at birth [deficiency (<30 nmol/l), insufficiency (30−50 nmol/l) and sufficiency (>50 nmol/l)]. Neonatal biochemical and anthropometric profiles and maternal demographic, social, dietary and biochemical profiles were comparatively evaluated between the three groups. Univariate and multivariate logistic regression was performed to identify independent associations of maternal factors with neonatal vitamin D status. Vitamin D deficient-neonates manifested higher parathyroid hormone (7.20 ± 2.60 vs 5.50 ± 1.50 pg/ml, p = 0.01) and lower corrected calcium (10.70 ± 0.70 vs 11.30 ± 1.30 mg/dl, p = 0.02) concentrations compared with vitamin d -insufficient neonates. Mothers of vitamin D deficient and insufficient neonates had a lower total of 25(OH)D (31.7 ± 19.2 and 36.5 ± 22.3 vs 53.3 ± 39.0 nmol/l, p < 0.01) and 25(OH)D3 (27.4 ± 17.5 and 33.3 ± 19.9 vs 47.3 ± 36.7 nmol/l, p < 0.01 and p = 0.04, respectively) concentrations respectively, compared with those of vitamin D-sufficient neonates. Maternal use of alcohol during pregnancy was associated with a 5.57-fold higher risk for neonatal vitamin D deficiency at birth (OR 5.57, 95 % CI1.17–26.56, p = 0.03). Newborns with vitamin D deficiency presented a 6.89-fold higher risk of having been given birth by vitamin D deficient mothers (OR 6.89, 95 % CI 3.09–15.38, p < 0.01). In conclusion, neonatal vitamin D deficiency is associated with maternal 25(OH)D concentrations at birth and maternal alcohol use. Further studies are required to replicate these findings in other regions and populations.